Determination of Phosphate-activated Glutaminase Activity and Its Kinetics in Mouse Tissues using Metabolic Mapping (Quantitative Enzyme Histochemistry). (November 2014) - Botman, Dennis; Tigchelaar, Wikky; Van Noorden, Cornelis J.F.
Phosphate-activated glutaminase (PAG) converts glutamine to glutamate as part of the glutaminolysis pathway in mitochondria. Two genes, GLS1 and GLS2, which encode for kidney-type PAG and liver-type PAG, respectively, differ in their tissue-specific activities and kinetics. Tissue-specific PAG activity and its kinetics were determined by metabolic mapping using a tetrazolium salt and glutamate dehydrogenase as an auxiliary enzyme in the presence of various glutamine concentrations. In kidney and brain, PAG showed Michaelis-Menten kinetics with a Km of 0.6 mM glutamine and a Vmax of 1.1 µmol/mL/min when using 5 mM glutamine. PAG activity was high in the kidney cortex and inner medulla but low in the outer medulla, papillary tip, glomeruli and the lis of Henle. In brain tissue sections, PAG was active in the grey matter and inactive in myelin-rich regions. Liver PAG showed allosteric regulation with a Km of 11.6 mM glutamine and a Vmax of 0.5 µmol/mL/min when using 20 mM glutamine. The specificity of the method was shown after incubation of brain tissue sections with the PAG inhibitor 6-diazo-5-oxo-L-norleucine. PAG activity was decreased to 22% in the presence of 2 mM 6-diazo-5-oxo-L-norleucine. At low glutamine concentrations, PAG activity was higher in periportal regions, indicating a lower Km for periportal PAG. When compared with liver, kidney and brain, other tissues showed 3-fold to 6-fold less PAG activity. In conclusion, PAG is mainly active in mouse kidney, brain and liver, and shows different kinetics depending on which type of PAG is expressed.